A retrospective analysis of risk factors of oromaxillofacial infection in patients presenting to a hospital emergency ward - Jinyoung Park; Jae-Yeol Lee; Dae-Seok Hwang; Yong-Deok Kim; Sang-Hun Shin; Uk-Kyu Kim; Jae-Min Song (SpringerOpen, 2019)
Abstract Background The purpose of this study was to review the clinical features of oromaxillofacial infections in patients presenting to a hospital emergency ward, to identify the key factors affecting the requirement for hospitalization, and the potential risk factors predisposing to a prolonged length of hospital stay. Methods A retrospective medical record review of the 598 patients treated for oromaxillofacial infection from 2013 to 2017 at the oral and maxillofacial surgery department, Yangsan Pusan National University Hospital, was conducted. The following information was collected from each patient: sex, age, past medical history, site of infection, etiology, admission or outpatient care, level of C-reactive protein (mg/dL), fascial spaces involved, treatment method, and duration of hospitalization. Chi-squared tests were used to identify risk factors, which were further analyzed using multivariable logistic regression. Results A total of 606 patients were eligible for inclusion in the study, of which eight were excluded due to having incomplete charts; thus, 598 patients were included: 55% were male, mean patient age was 47.1 ± 19.9 years, and 12.9% of patients were diabetic. Furthermore, 71.2% of patients had infection originating in the mandible; the most common tooth of origin was lower posterior, and 29.8% of patients were hospitalized. Risk factors for hospital admission were elderly patients with concurrent disease, elevated C-reactive protein level, and multiple-space infection in the oromaxillofacial area. The duration of hospitalization was correlated with both diabetes and age. Conclusions The requirement for hospital admission is determined by the severity of the infection; even severe infections, once treated with appropriate surgery, have no relation to the length of hospital stay. The important risk factors for increased duration of hospitalization are diabetes mellitus and older age. The understanding of risk factors associated with a prolonged hospital stay during the treatment of oromaxillofacial infection will aid in treatment planning as well as highlight the importance of adequate diabetes control in patients at risk of such infection.